2000
DOI: 10.1046/j.1537-2995.2000.40101223.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukapheresis components may be cryopreserved at high cell concentrations without additional loss of HPC function

Abstract: The cryopreservation of PBPC components at standard concentrations and 3.3 (1.8-6.2)-fold cell concentrations has no adverse effect on the function of HPCs after thawing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 15 publications
4
39
0
1
Order By: Relevance
“…Thus the incidence of acute or chronic GVHD was not compared between the fresh and cryopreserved cohorts; overall the incidence of chronic GVHD is very low in our haplocord transplants. Some studies have shown that cryopreserved PBSCs at concentrations higher than 2 × 10 8 cells/mL can cause cell viability loss, but CD34+‐selected products have very low cell concentration (<1 × 10 5 cells/mL).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the incidence of acute or chronic GVHD was not compared between the fresh and cryopreserved cohorts; overall the incidence of chronic GVHD is very low in our haplocord transplants. Some studies have shown that cryopreserved PBSCs at concentrations higher than 2 × 10 8 cells/mL can cause cell viability loss, but CD34+‐selected products have very low cell concentration (<1 × 10 5 cells/mL).…”
Section: Discussionmentioning
confidence: 99%
“…10,[12][13][14] Recent reports in the literature describe fewer adverse reactions to infusion with lower DMSO concentrations. 15 Detailed cryopreservation protocols are available from published manuscripts and book chapters [16][17][18] and from the International Society of Cellular Therapy (ISCT) and AABB professional association websites 19,20 and from their members.…”
Section: Personnelmentioning
confidence: 99%
“…Increasing the cell concentration in the autograft and thereby reducing both the autograft volume and the amount of DMSO needed for cryopreservation is a simple strategy (Cabezudo et al, 2000;Martin-Henao et al, 2005;Rowley et al, 1994). The final mononuclear cell concentration in the autografts varies between transplantation centers; the most common concentration being 2 × 10 8 /mL (Windrum et al, 2005).…”
Section: Reduction Of the Autograft Volume And Increasing The Cell Comentioning
confidence: 99%
“…Some centres use higher and some use lower concentrations (for example 1 × 10 8 /mL), whilst others do not have any limits (Windrum et al, 2005). Several reports describe cryopreservation with high cell concentrations not resulting in additional loss of hematopoietic progenitor cell function, and not impairing the hematopoietic reconstitution (Cabezudo et al, 2000;Rowley et al, 1994), despite lower viability in samples with high concentration; 0.9 (range: 0.6-1) versus 2.9 (range: 2.2-4.7) × 10 8 /mL (Cabezudo et al, 2000). Reduction of the autograft volume by centrifugation prior to cryopreservation of the stem cells, as we performed, results in lower autograft volumes that will consequently require reduced amounts of DMSO for cryopreservation (Akkok et al, 2009).…”
Section: Reduction Of the Autograft Volume And Increasing The Cell Comentioning
confidence: 99%